E3SM - Drake Passage Transport, 26.5 AMOC, Northward Heat Transport at 26.5N, from Hewitt et al 2020 - Van Roekel, Luke (Zenodo, 2020)
E3SM monthly output has been annually averaged and processed to derive the maximum overturning at 26.5 N, the northward heat transport at 26.5N and the drake passage transport. The model output includes the low resolution configuration and high resolution configuration. Both runs use the 1950 control from the HighResMIP protocol.